Hearing loss and work participation: a cross-sectional study in Norway. (2nd September 2018) - Svinndal, Elisabeth Vigrestad; Solheim, Jorunn; Rise, Marit By; Jensen, Chris
Abstract: Objective: To study work participation of persons with hearing loss, and associations with hearing disabilities, self-reported workability, fatigue and work accommodation. Design: Cross-sectional internet-based survey. Study sample: A total of 10, 679 persons with hearing loss within working-age were invited to answer the survey, where 3330 answered (35.6%). Results: Degree of hearing loss was associated with low workability, fatigue and work place accommodation, while sick leave was associated with fatigue. Degree of hearing loss was positively associated with being unemployed ( p < .001) and having part-time work ( p < .01) (often combined with disability benefits) for women. Work place accommodation was more frequently provided among respondents working with sedentary postures, high seniority, long-term sick leave or low workability. Additional unfavourable sensory conditions were associated with decreased employment ( p < .001) and workability, and an increase in sick leave ( p < .01) and fatigue ( p < .001). Conclusions: Hearing loss seemed to influence work participation factors negatively; particularly, for moderate hearing loss and for women, even though the degree of employment was high. A lack of work place accommodation when there was a need for such was found. This implies increased attentiveness towards individual needs concerning the experienced disability a hearing loss may produce. A more frequent use of hearing disability assessment is suggested.